2019
DOI: 10.1364/oe.27.002656
|View full text |Cite
|
Sign up to set email alerts
|

Single-shot extreme-ultraviolet wavefront measurements of high-order harmonics

Abstract: We perform wavefront measurements of high-order harmonics using an extremeultraviolet (XUV) Hartmann sensor and study how their spatial properties vary with different generation parameters, such as pressure in the nonlinear medium, fundamental pulse energy and duration as well as beam size. In some conditions, excellent wavefront quality (up to λ/11) was obtained. The high throughput of the intense XUV beamline at the Lund Laser Centre allows us to perform single-shot measurements of both the full harmonic bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 43 publications
2
11
0
Order By: Relevance
“…59 and further down in this work, according to ref. 66 , they may introduce distortions in XUV wavefront and hence influence the duration of the emitted attosecond pulses at the "end station" where the XUV beam is refocused. This matter will be further discussed in Section 4 of the manuscript.…”
Section: The High Xuv Photon Flux Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…59 and further down in this work, according to ref. 66 , they may introduce distortions in XUV wavefront and hence influence the duration of the emitted attosecond pulses at the "end station" where the XUV beam is refocused. This matter will be further discussed in Section 4 of the manuscript.…”
Section: The High Xuv Photon Flux Sourcementioning
confidence: 99%
“…An additional effect to be considered is pointed out recently in refs. 66,68 . Different harmonics, due to their different divergence are focused at different positions, have different focal spots and therefore lead to only partial spatial overlap of the superimposed harmonics and to different Gouy phase contributions in the harmonic superposition.…”
Section: Temporal Characterization Of the Attosecond Pulse Trainsmentioning
confidence: 99%
“…Previous studies [30,[32][33][34][35][36] have shown that high-order harmonics have different wavefronts at the exit of the nonlinear medium, which can be convergent or divergent [35], corresponding to a real or virtual focus, respectively. The wavefront curvature of the harmonics is the sum of that of the driving laser and an additional contribution originating from the process behind the generation of high-order harmonics.…”
Section: Introductionmentioning
confidence: 99%
“…The former measures the relative position change of the geometrical center of intensity for each pinhole in the Hartmann array in order to obtain an estimate of the local slope of the wavefront. The technique is well-known and has been used in a large number of laboratories for real-time beam characterization, laser-aberration description, and optics alignment [25][26][27]. The centroid method was specifically carried out with Imagine Optic software WaveView.…”
Section: Analysis Approachmentioning
confidence: 99%